Intensive English Course in Online Class Through WhatsApp and English Discovery as MALL Platform in Speaking - Waode Hamsia (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
Technology in education is used as a tool to achieve learning goals. The utilization of technology in the field of education can make it easier to get information. This research aimed to investigate the utilization of technology to find out how students respond to using WhatsApp as a Mobile-Assisted Language Learning (MALL) platform in learning outcomes in speaking skills. The researcher used a narrative qualitative method as a research design which came from observation, questionnaires, and interviews. Moreover, the research design for the students’ responses observed the teaching-learning process. The subjects of this research were 20 students in the second semester of the academic year 2022/2023 at Universitas Muhammadiyah Surabaya. This research showed that WhatsApp as a Mobile-Assisted Language Learning (MALL) platform makes students interested in and enjoy learning English through Intensive English Courses in online classes. Therefore, this learning medium is online learning with a collection of substances open on the English Discoveries platform. In online learning, speakers can check how understudy learning comes about particularly through the Teacher Management System (TMS) hence, teachers can continuously grant input for each student’s online learning advance. Since they can learn anywhere and anytime that was as a new experience in learning English for their daily activities in speaking ability.